Coronary artery stretch versus deep injury in the development of in-stent neointima. Issue 4 (1st October 2002) - Gunn, J; Arnold, N; Chan, K H; Shepherd, L; Cumberland, D C; Crossman, D C
Abstract : Objective: To investigate the relative importance of stent induced arterial stretch and deep injury to the development of in-stent neointima. Setting: Normal porcine coronary arteries Methods: 30 BiodivYsio stents (Biocompatibles) were deployed at a stent to artery ratio of 1.25:1 (a moderate injury) and harvested at 28 days. Multiple serial cross sections were analysed morphometrically and the neointimal areas were correlated with the type and degree of injury. Results: Arterial stretch occurred in 78% of struts (77% of sections) and produced moderate neointimal growth (neointimal area 1.93 (0.13) mm 2 ). Deep injury (rupture of the internal elastic lamina) occurred in 20% of struts (23% of sections) and produced a 1.7-fold increase in neointimal area (3.33 (0.41) mm 2 ) compared with stretch only (p = 0.0002). With even deeper injury (rupture of the external elastic lamina), there was a 2.6-fold increase in neointimal area (5.01 (0.48) mm 2 ) compared with stretch only (p = 0.02). A new injury score, incorporating both stretch and deep injury, correlated with neointimal area ( r = 0.60, p < 0.001). Conclusions: Stretch of the coronary artery in a stent is common, and a major contributor to neointima formation, even in the absence of deep injury. Deep injury is, however, a more potent stimulus to neointima formation than stretch. Greater degrees of stretch are associated with thicker neointima. Where neither deep injury nor stretch are seen, the stent has no effect upon the development of neointima.